Computer analysis of oxygen adsorption at SnO2 thin films - Izydorczyk, Weronika; Adamowicz, Bogusława (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
An influence of oxidation of SnO2 thin films on depletion layer electronic parameters and film conductance has been studied by means of computer simulations. The surface potential value and in-depth potential profiles in the depletion region have been obtained by solving the Poisson–Boltzmann equation in the case of grains with slab geometry and different doping. The SnO2 grain thickness was in the range from 20 to 500 nm. The surface coverage by oxygen ions (O2-, O-) as well as film conductance per square and its sensitivity versus temperature (from 300 to 900 K) have been rigorously calculated. The effect of donor (oxygen vacancies) mobility and degree of donor ionisation has been taken into account.
Optica Applicata, Vol. 37, 2007, nr 4, s. 377-385
Keywords: optyka; SnO2 thin films; nanolayers; oxygen adsorption; depletion layer; modeling of sensor structures